The role of serotonin in haemostasis - Duerschmied, D.; Bode, C. (Hämostaseologie, 2009)
Serotonin is transported by platelets and released upon activation. This induces constriction of injured blood vessels and enhances platelet aggregation to minimize blood loss. Consequently, serotonin receptor antagonists have been tested for their anti-ischemic potency in atherothrombotic disease. Unfortunately, the results have been contradictory. Recent murine studies found that activation of the platelet serotonin receptor induces shedding of important adhesion molecules. As a consequence, platelets lose their ability to contribute to thrombus formation and may be cleared from the circulation. Serotonin effects on platelets are not only mediated by receptor binding but also by covalently binding effector proteins (serotonylation) in the platelet cytoplasm and on the platelet surface. In conclusion, the effects of serotonin on haemo -stasis are complex and new antithrombotic strategies have to account for this complexity.
Keywords: Serotonin; platelets; serotonylation; haemostasis; vasoconstriction